Advancements in Gene-Based Therapeutic Angiogenesis for Chronic Limb-Threatening Ischemia - Wang, Peng; Di, Xiao; Li, Fengshi; Rong, Zhihua; Lian, Wenzhuo; Sun, Guoqiang; Liu, ChangWei; Ni, Leng (Human gene therapy, 2025)
The objective of this article is to summarize the research progress and discuss the current difficulties of gene-based therapeutic angiogenesis in lower limb ischemic diseases, so as to provide new research directions for the non-invasive treatment of lower limb ischemia. The basic and clinical trials of gene-based therapeutic angiogenesis in lower limb ischemia in recent years were read and reviewed. Growth factors such as vascular endothelial growth factor, hepatocyte growth factor, and fibroblast growth factor have been extensively studied for their application in lower limb ischemic diseases. However, clinical studies across various phases have shown inconsistent efficacy endpoints. The efficacy of gene therapy remains questionable. Before exploring efficient methods of delivering pro-angiogenic genes to ischemic tissues, clarification is needed regarding whether the goal of gene therapy is to simply promote collateral circulation or create a conducive tissue microenvironment for angiogenesis. In conclusion, pre-clinical and clinical studies have demonstrated the potential of therapeutic angiogenesis, but more systematic and comprehensive research is needed to explore safer, more effective, and cost-effective treatment methods.